Metal-free Catalysts for Oxygen Reduction in Alkaline Electrolytes: Influence of the Presence of Co, Fe, Mn and Ni Inclusions - Masa, Justus; Zhao, Anqi; Xia, Wei; Muhler, Martin; Schuhmann, Wolfgang (Electrochimica Acta, 2014)
Metal-free nitrogen modified carbon catalysts (NC) are very closely related to MNC catalysts which contain a transition metal(s) (M), usually Fe or Co as an essential constituent. We investigated the influence of metal inclusions on the activity of nitrogen-doped carbon black in the electrocatalysis of the oxygen reduction reaction (ORR). A reference metal-free NC catalyst was prepared by pyrolysis of a polypyrrole/Vulcan XC72 composite at 800 °C for 2 h under helium. Controlled amounts of Co, Fe, Mn and Ni in low concentrations were then introduced into NC by impregnating it with the corresponding meso-tetra(4-pyridyl) porphyrin metal complex followed by further pyrolysis at 650 °C for 2 h under helium. The resulting catalysts were investigated for ORR using rotating disk electrode and rotating-ring disk electrode voltammetry in 0.1 M KOH. Additionally, the rate of decomposition of hydrogen peroxide by the different catalysts was determined in order to probe the influence of the metal inclusions on the mechanism and selectivity of the ORR. The results show that Fe, Co and Mn inclusions cause a substantial decrease of the overpotential of the reaction and enhance the catalytic current, whereas the presence of Ni has a poisoning effect on ORR. In the presence of Fe, the catalysts apparently reduce oxygen selectively to OH− in a direct four electron transfer process as opposed to the two-step, two electron pathway involving hydrogen peroxide as an intermediate for the case of the NC catalyst.
Keywords: Metal-free catalysts; oxygen reduction; nitrogen modified carbon; metal inclusions